Meningkatkan Disiplin Guru dalam Kehadiran Mengajar di Kelas melalui Penerapan Reward and Punishment di MTs Darul Ulum Nglumber Kepohbaru Bojonegoro - Razak, Abdul (MANAGIERE: Journal of Islamic Educational Management, 2023)
Improving the quality of learning in madrasas depends on several factors. A very important factor includes the application of madrasa culture towards improving quality. Madrasah culture is a positive thing that must be maintained and implemented by all madrasah residents without feeling forced. One of the Madrasa cultures that must be maintained is the issue of discipline, including the discipline of teachers in their presence in class during the teaching and learning process. To improve teacher discipline, efforts can be made in various ways. In this School Action Research (PTS), action was attempted in the form of implementing Reward and Punishment for teachers at MTs Darul Ulum Nglumber Kepohbaru Bojonegoro. This research was carried out in two cycles because, from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in attendance in the classroom the teaching and learning process increased and met the indicators that had been set at 75%. From the results of this research, it can be concluded that improving teacher discipline in class attendance during teaching and learning activities can be done by implementing Rewards and Punishment for teachers.